2013
DOI: 10.2341/11-057-l
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surface Treatments on Microtensile Bond Strength of Repaired Aged Silorane Resin Composite

Abstract: SUMMARY Objective: This laboratory study compared the repaired microtensile bond strengths of aged silorane resin composite using different surface treatments and either silorane or methacrylate resin composite. Methods: One hundred eight silorane resin composite blocks (Filtek LS) were fabricated and aged by thermocycling between 8°C and 48°C (5000 cycles). A control (solid resin composite) and four surface treatment groups (no treatment, acid treatment, aluminum oxide sandblasting, and diamond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
23
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 21 publications
6
23
1
4
Order By: Relevance
“…SEM and AFM images in the present study confirmed roughening of the substrate surface and explained the increased repair bond strength after diamond bur surface preparation. Contrary to this study, Palasuk et al reported that use of a diamond bur did not result in a significant increase in repair bond strength of silorane-based composite resin (9). In addition, in a study by Loomans et al , there was no significant difference in repair bond strength of heavily hybrid Clearfil PhotoPosterior composite resin between the control group (with no surface preparation) and the group prepared with a diamond bur (4).…”
Section: Discussioncontrasting
confidence: 94%
See 3 more Smart Citations
“…SEM and AFM images in the present study confirmed roughening of the substrate surface and explained the increased repair bond strength after diamond bur surface preparation. Contrary to this study, Palasuk et al reported that use of a diamond bur did not result in a significant increase in repair bond strength of silorane-based composite resin (9). In addition, in a study by Loomans et al , there was no significant difference in repair bond strength of heavily hybrid Clearfil PhotoPosterior composite resin between the control group (with no surface preparation) and the group prepared with a diamond bur (4).…”
Section: Discussioncontrasting
confidence: 94%
“…The results of the present study showed that the repair bond strength of giomer after mechanical surface treatments (air abrasion, Nd:YAG laser and diamond bur) increased significantly, which is consistent with the results of previous studies on resin-based materials, indicating that mechanical roughening of the substrate surface is an important factor in increasing the repair bond strength (9-11,17). An increase in repair bond strength might be attributed to an increase in surface roughness of the substrate and an increase in bonding surface, as confirmed by SEM and AFM images.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the present study, although repaired with methacrylate-based material, the group with silorane-based material showed predominance of adhesive failures. A previous study showed that after aluminum oxide sandblasting, the aged silorane resin repaired with either silorane resin composite with Filtek LS system adhesive or methacrylate resin composite with methacrylate dental adhesive presented primarily adhesive failures in all groups (20).…”
Section: Discussionmentioning
confidence: 99%